Finite element analysis and experimental investigations of the intervertebral disc in the human lumbar, cervical spine and porcine lumbar spinal segment - Ciach, Michal; Awrejcewicz, Jan (Computer Assisted Methods in Engineering and Science, 2023)
The main objective of this study is to design three-dimensional geometrical and mechanical finite element model of the intervertebral disc between L2-L3 vertebras in the lumbar and C5- C6 cervical spinal segment. The model was directed toward understanding the work and the role of the intervertebral disc that performs in the human spinal segment body. The three-dimensional finite element motion segment was developed and its response to different loads was performed. The model accounted for the solid component of the nucleus pulposus while anulus fibrosus was modeled as a matrix of homogeneous ground substance reinforced by anulus fibers. End plates similarly to the nucleus pulposus were simulated using volumic elements. Simultaneously the vertebral bodies have been modeled as a complex construction of a cancellous core covered by a cortical shell of the orthotropic material properties. Isotropic material has been used to model posterior elements. To simulate ligament like behavior, tension only elements have been used. Numerical studies of the lumbar segment have been consequently compared with the experimental investigation performed on the porcine model by authors and other in vitro experiments on human lumbar spine accomplished by other scientists. In cervical spinal segment numerically two surgical techniques (Cloward and Robinson- Smith) have been tested. Two types of loads have been applied to three models - to an intact C5- C6 spinal segment and then to the vertebras after performing those two surgical techniques. All numerical analysis have been undertaken using ANSYS 5.4 commercial application.